OPTICAL SPECTRA OF CO2+ IN THREE SYNTHETIC SILICATE MINERALS - Taran M.N.; Rossman G.R. (My University, 2001)
Polarized optical absorption spectra of three synthetic Co-bearing silicates, orthopyroxene, olivine and beryl, were studied at room and liquid nitrogen temperatures. In all three matrices, Co enters octahedral structural sites as the Co2+ ion. In accordance with the d7 electronic energy level diagram, the spectra show three distinct band systems which are assumed to originate from three spin-allowed dd transitions of Co2+, 4T1g(4F) →4T2g(4F), 4T1g(4F) →4A2g(4F), and 4T1g(4F) →4T1g(4P). The number of bands is different in different matrices and is regulated by the splitting of electronic states, symmetry selection rules for electronic transitions between them, and Co2+ ion distribution between non-equivalent structural sites. Due to a strong preference of Co2+ for the M2 site and the greater intensities (oscillator strengths) of electronic dd transitions for Co2+ in the M2 site, M2 Co2+ bands prevail in the (Mg,Co)SiO3 orthopyroxene spectra. In olivines, the number of bands is larger than in orthopyroxene due to the combined contribution of both M1 Co2+ and M2 Co2+ ions. By comparison of the (Mg,Co)2SiO4 and Co2SiO4 olivine spectra, the bands caused by M1 Co2+ and M2 Co2+ were distinguished. The spectra of Co-bearing beryls, Be3Al2[Si6O18], prepared by both flux and hydrothermal growth, indicate that Co enters the structure mostly as Co2+ in the octahedral Alsite.